BLADDER SYMPTOMS IN CHILDREN WITH FUNCTIONAL CONSTIPATION : SYSTEMATIC REVIEW - Prahasari Wismawan, Made Nindya; Susma Sugara, I Gede Deden (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Functional constipation (FC) affects 3% of children worldwide. FC occurs in 95% of children without an organic reason. Lower urinary tract symptoms (LUTS) and urinary tract infection (UTI) often co-occur. The International Children's Continence Society (ICCS) coined the term bladder and bowel dysfunction (BBD) to stress the frequent combination of bladder and bowel issues.Aim: The purpose of this research is to investigate bladder symptoms in children with functional constipation.Methods: This study confirmed that it met all of the requirements by evaluating the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 criteria. This allowed the researchers to guarantee that the study was as current as possible. Publications that were published between 2015 and 2023 were incorporated into the search strategy, which encompassed a number of different electronic reference databases (including Pubmed and SagePub). We did not consider review papers, duplicate publications, or articles that were only partially written. Result: PubMed database search results yielded 213 articles, while SagePub database search results yielded 112 articles. In 2015, the search results for SagePub returned 13 articles while PubMed returned 19 articles. We compiled a total of eight articles (6 from PubMed and 2 from SagePub) and included three studies that met the inclusion criteria. Conclusion: We can't say for sure how often bladder problems show up in children with FC. This is because the frequency varies a lot, so there aren't many studies. However, children with FC do often have bladder complaints.